Co-constituting narrative: the role of researcher identity bids in qualitative interviews with women ex-offenders - Wesely, Jennifer K. (Criminal justice studies, 2018)
Narrative criminology draws upon the stories of the research participants to better understand crime. These narratives are shaped not only by a range of structural, institutional and individual factors, but by dynamics within the interview itself. As both participant and interviewer deploy narrative techniques, they co-constitute identity meanings during the interview process. This study examines interviews with 30 women recently released from incarceration to identify ways that the researcher constructed and “bid” for identity meanings through narrative during the interview process. Specifically analyzed are the researcher’s “small stories” put forth in response to participants during the interview exchange. Ultimately, the co-constitutive nature of interview dynamics suggest that the researcher’s identity bids via small stories have implications for how participants assert their own identity meanings, account for their experiences, and ultimately orient or conceptualize their futures.